(untitled) (Revista Brasileira de Iniciação Científica, 2024)
The beginning of teaching is a crucial phase for the permanence or abandonment of the profession, in which feelings recognized as reality shock, survival and discovery are experienced. At the same time, in undergraduate degrees, PIBID stands out for providing students with opportunities to enter professional contexts. In this text, we bring these realities closer together, analyzing in the reports of a PIBID graduate the similarities between his experiences and the characteristics inherent to the beginning of his career. The qualitative research was based on Bardin’s perspective of content analysis, establishing the feelings presented as previous categories. We observed a convergence of these experiences and indicated the systematized incorporation of PIBID records as a source of learning about the career in the teaching degree, aiming at a safer entry into the profession.